2014
DOI: 10.1002/yea.3053
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced deacidification activity in Schizosaccharomyces pombe by genome shuffling

Abstract: A problem frequently occurring in making some kinds of wines, particularly Vitis quinquangularis Rehd wine, is the presence of malic acid at high concentrations, which is detrimental to the quality of wines. Thus, there is a need of the ways for effectively reducing the malic acid levels in wine. This study aimed to generate shuffled fusants of Schizosaccharomyces pombe with enhanced deacidification activity for reducing the excessive malic acid content in wine. Sz. pombe CGMCC 2.1628 was used as the original … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 30 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…Apart from traditional screening, genetic modification techniques are also capable of creating new yeast strains with specific metabolic profiles for alcoholic fermentation (Krogerus et al, 2017). Ding et al (2015) enhanced deacidification activity in Schizosaccharomyces pombe using genome shuffling, and Dong et al (2019) increased production of acetate ester in S. cerevisiae using a "self-cloning" integration strategy. Ohashi et al (2020) reported that the removal of feedback inhibition of NAGK activity resulted in the significantly higher production of ornithine in sake and sake cake by gene expression.…”
Section: Fermentation Starter Of Yeastmentioning
confidence: 99%
“…Apart from traditional screening, genetic modification techniques are also capable of creating new yeast strains with specific metabolic profiles for alcoholic fermentation (Krogerus et al, 2017). Ding et al (2015) enhanced deacidification activity in Schizosaccharomyces pombe using genome shuffling, and Dong et al (2019) increased production of acetate ester in S. cerevisiae using a "self-cloning" integration strategy. Ohashi et al (2020) reported that the removal of feedback inhibition of NAGK activity resulted in the significantly higher production of ornithine in sake and sake cake by gene expression.…”
Section: Fermentation Starter Of Yeastmentioning
confidence: 99%
“…Several research teams are studying the winemaking potential of non- Saccharomyces yeast strains [ 1 ]. For example, fission yeasts from the genus Schizosaccharomyces show more rapid malic acid deacidification, by converting malic acid to ethanol and CO 2 [ 2 4 ]. Schizosaccharomyces pombe possesses several remarkable metabolic properties that may be useful in modern quality winemaking [ 2 , 5 6 ], including a malic dehydrogenase activity, high autolytic polysaccharides release [ 7 ], ability of gluconic acid reduction [ 8 11 ], urease activity [ 12 , 13 ], elevated production of pyruvic acid and colour improvement [ 14 , 15 ], as well as low production of biogenic amines and ethyl carbamate [ 6 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Metabolic engineering undertakes a rational approach to redirect the metabolic fluxes towards the desired product by targeted manipulation of the cell’s genome involving insertion of heterologous pathways, overexpression and downregulation of multiple genes, construction of synthetic regulatory circuits, etc. [ 14 , 24 ]. Multiple rounds of genetic engineering are commonly required until the cell with desired properties is obtained.…”
Section: Introductionmentioning
confidence: 99%
“…A series of vectors with various auxotrophic markers, promoters, multiple cloning sites and integration sequences have been developed [ 9 , 15 , 38 , 47 ]. Recently, an EasyClone vector set was developed [ 17 ] enabling integration by double cross-over events into several intergenic regions, which have been validated for sufficient and reliable expression level and absence of growth impairment, on three different S. cerevisiae chromosomes [ 24 ]. The insertion sites are interspaced with essential genes voiding risk of chromosomal rearrangements even when the expression cassettes share long sequence homologies [ 26 ].…”
Section: Introductionmentioning
confidence: 99%